Anaís: uma criança à frente do teste - Frizzo, Rafaela Joaquim (2022)
Introduction: Congenital heart diseases occur in the gestational period, considered a moment of great emotional sensitivity of the future mother, aggravated by the symbolism that is attributed to the heart. In addition, children diagnosed with hypoplastic heart disease may experience delays in the most diverse areas of neuropsychomotor and language development, by the effects of the disease, by the surgeries to which they are submitted throughout childhood and by the required hospitalization time. Objective: to understand and analyze the effects of congenital heart disease on the constitution and development of a child, as well as to intervene clinically to transform and/or modify the evaluation results. Method: a descriptive clinical case study, with quantitative and qualitative analysis of different data collected from a child with heart disease with barriers in the development process in general and in language acquisition. Procedures and materials used: interview with the child's mother (recorded and transcribed) with signature of the informed consent form and signature of the image use term; recording of meetings; field journal; application of the Revised Psychoeducational Profile (PEP-R) instrument. Results: a) in the quantitative part: Anais reached 87 points on the PEP-R development scale, which indicates a neuropsychomotor delay of 01.06 years, with language being the most compromised area; on the behavior scale: the results were adequate” for the area of relationship and affection; in the others, it oscillated between “adequate” and “moderate”. It is worth noting that the area of language has a “moderate” result, confirming what was found in the behavior scale; b) in the qualitative part, the analysis of transcribed fragments from the videos showed significant differences in Anais' responses to the test, before and after the researcher changed her posture during the application. Discussion: by considering the transference process and the change of attitude of the evaluator sensitive to the subject's listening, it was possible for the emergence of Anais's subjectivity manifested in skills in development or about to emerge. Final considerations: we can say that Anais is ahead of the test, in the sense of refusing the results obtained in the first application, performed according to the PEP-R manual. As much as some areas remain out of step, the participant showed a transformation in her answers, with a change of approach. Therefore, the test is effective for children with language acquisition impasses if the evaluator is not restricted to parameterizing the development and clinically intervenes in parallel with the evaluation